Probing the circumnuclear absorbing medium of the buried AGN in NGC 1068 through NuSTAR observations. Issue 3 (15th January 2020) - Zaino, A; Bianchi, S; Marinucci, A; Matt, G; Bauer, F E; Brandt, W N; Gandhi, P; Guainazzi, M; Iwasawa, K; Puccetti, S; Ricci, C; Walton, D J
ABSTRACT: We present the results of the latest NuSTAR monitoring campaign of the Compton-thick Seyfert 2 galaxy NGC 1068, composed of four ∼50 ks observations performed between 2017 July and 2018 February to search for flux and spectral variability on time-scales from 1 to 6 months. We detect one unveiling and one eclipsing event with time-scales less than 27 and 91 d, respectively, ascribed to Compton-thick material with N H  = (1.8 ± 0.8) × 10 24 and ≥ (2.4 ± 0.5) × 10 24 cm −2 moving across our line of sight. This gas is likely located in the innermost part of the torus or even further inward, thus providing further evidence of the clumpy structure of the circumnuclear matter in this source. Taking advantage of simultaneous Swift –XRT observations, we also detected a new flaring ULX, at a distance d  ∼ 30 arcsec (i.e. ∼2 kpc) from the nuclear region of NGC 1068, with a peak X-ray intrinsic luminosity of (3.0 ± 0.4) × 10 40 erg s −1 in the 2–10 keV band.